Communications skill and virtual micro-guiding: Competency development strategies for Hajj guides in Islamic universities - Hasanah, Hasyim; Anas, Ahmad; Silvi, Firda Aricha; Nurbini (Islamic Communication Journal, 2025)
This study is motivated by the importance of developing the competency of candidate Hajj ritual guides, amidst the high interest in going to the Hajj, but not supported by the availability of competent resources to guide the congregation. On the other hand, the format for competency development in Islamic colleges is still not uniform, so an ideal competency development strategy based on communication skills and virtual micro-guiding is needed. This study aims to describe and analyze communication skills and virtual micro-guiding as a strategy for developing the competency of candidate professional Hajj ritual guides. This study is operationalized through qualitative analysis of critical interaction models. Data was collected from 87 candidate Hajj guides in the Department of Hajj and Umrah Management. The data results are in the form of persuasive communication practices, virtual micro-guiding from the results of in-depth interviews, and documentation studies. This study found a form of skill consisting of persuasive communication and therapeutic communication. The virtual micro-guiding form is operationalized with virtual group guiding, support group, group counseling, and teaching group devices. The implications of persuasive and therapeutic communication skills are directed at efforts to understand the Hajj ritual. Meanwhile, the implications of virtual micro-guiding are one of the national policies in developing competencies by implementing a conducive communication environment. This is the first study to examine communication skills and virtual micro-guiding as competency development strategies for hajj guides. ***** Studi ini dilatarbelakangi pentingnya pengembangan kompetensi calon pembimbing manasik haji, ditengah animo pergi haji yang masih tinggi, namun tidak didukung ketersediaan sumber daya kompeten untuk membimbing jemaah. Di sisi lain, format pengembangan kompetensi di Perguruan Tinggi Islam masih tidak seragam, sehingga dibutuhkan strategi ideal pengembangan kompetensi berbasis keterampilan komunikasi dan virtual micro-guiding. Studi ini bertujuan mendeskripsikan serta menganalisis keterampilan komunikasi dan virtual micro-guiding sebagai strategi pengembangan kompetensi calon pembimbing manasik haji profesional. Studi ini dioperasionalkan melalui analisis kualitatif model interaksi kritis. Data dihimpun dari calon pembimbing haji di Prodi Manajemen Haji Umrah sebanyak 87 orang. Hasil data berupa praktek komunikasi persuasif, virtual micro-guiding dari hasil wawancara mendalam dan studi dokumentasi. Studi ini menemukan bentuk keterampilan yang terdiri dari komunikasi persuasif dan komunikasi terapiutik. Bentuk virtual micro-guiding dioperasionalkan dengan perangkat kelompok bimbingan virtual, kelompok dukungan, kolompok konseling, dan kelompok pengajaran. Implikasi keterampilan komunikasi persuasive dan terapiutik diarahkan pada usaha pemahaman ritualistic haji. Sedangkan implikasi virtual micro-guiding menjadi salah satu kebijakan nasional dalam pengembangan kompetensi dengan penerapan lingkungan komunikasi yang kondusif. Ini adalah studi pertama yang mengkaji keterampilan komunikasi dan bimbingan mikro virtual sebagai strategi pengembangan kompetensi pembimbing haji.